Dampak Harga dan Ulasan Produk terhadap Keputusan Pembelian di Shopee pada Mahasiswa Program Sarjana Universitas Sangga Buana YPKP Tahun 2024 - Mustahif, Ahmad; A Setiawan, Barick (Jurnal Digital Bisnis, Modal Manusia, Marketing, Entrepreneurship, Finance, & Strategi Bisnis (DImmensi), 2024)
This study aims to examine the influence and extent of the impact of price and product reviews on online purchasing decisions in Shopee’s E-commerce platform, specifically among students of Sangga Buana University YPKP Bandung in 2024. The research applies a quantitative approach with a correlational research method, using multiple linear regression to analyze the data. The sample consists of 100 students and Shopee consumers who have conducted purchase transactions on the Shopee platform, selected through random sampling. Data collection was carried out via a questionnaire. Results indicate a multiple linear regression model Y=13,530+0.095X1+0.515X2Y = 13,530 + 0.095 X1 + 0.515 X2Y=13,530+0.095X1+0.515X2. The F test results suggest that all independent variables collectively do not significantly affect online purchasing decisions. Additionally, a simple linear regression model was applied as H1 was rejected, resulting in Y=14.039+0.571X2Y = 14.039 + 0.571X2Y=14.039+0.571X2. The R Square value of 0.198 signifies that price and product review variables contribute 19.8% to online purchasing decisions, while the remaining 80.2% is influenced by other unexamined factors.